Cell Communication and Signaling - Birge, Raymond
Cell Communication and Signaling is an open access journal that encompasses all basic and translational aspects of cellular communications and signaling pathways in normal and pathological conditions. Genetic and epigenetic changes, cell-cell, cell-environment and cell-pathogen interactions often modulate or even override programmed patterns of cell behaviour. Cell signaling is therefore not only critical for normal cell growth and development, but abnormal signals are associated with numerous human diseases. Cell Communication and Signaling strongly encourages reports of studies incorporating molecular, morphological, biochemical, structural and cell biology approaches, as well as interdisciplinary work and innovative in silico, in vitro and in vivo models that facilitate investigations of cell signaling pathways, networks and cell behaviour.